Metamorphic evolution of the Río de la Plata Craton in the Cinco Cerros area, Buenos Aires Province, Argentina - Massonne, Hans-Joachim (2012)
A metapelite and an interlayered granite were studied from the Cinco Cerros area ca. 65 km WNW of the city of Mar del Plata. Garnet in these samples is slightly zoned with core and rim compositions of pyr 17(gro + andr) 6spes 1.5alm 75.5 and pyr 13.5(gro + andr) 5.5spes 2alm 80, respectively, in the metapelite. Corresponding compositions in the granite are pyr 15(gro + andr) 3.5spes 3.5alm 78 and pyr 11(gro + andr) 3.5spes 4.5alm 81. We used the PERPLE_X computer software package to calculate P-T pseudosections. From the pseudosection of the metapelite P-T conditions of 6.7 kbar and 670 °C were derived for an early metamorphic stage. Subsequently, a pressure release occurred at decreasing temperatures. The final metamorphic P-T conditions recorded by the studied rock are 4.5 kbar and 600 °C compatible with the absence of cordierite, staurolite, and an Al 2SiO 5-phase. Garnet in the granitoid crystallized between 715 and 690 °C at a pressure around 7.7 kbar.U-Th-Pb age dating with the electron microprobe was performed. 16 analyses of monazite in the metapelite formed three clusters resulting in ages of I: 2073 ± 11.4 (1 σ) Ma, II: 1913 ± 11.0 (1σ) Ma, and III: 1805 ± 20.8 (1 σ) Ma. Thus, the Paleoproterozoic metamorphic event can be related to the Trans-Amazonian cycle and was followed by slow cooling.As our study area is close to the margin of the Río de la Plata Craton, where abundant magmatic arc-derived plutonic rocks are outcropping, we interpret the derived P- T data as follows: A heating event (not recorded by the studied rocks) resulted from magmas that intruded during the Trans-Amazonian cycle. This event was followed by slow exhumation, probably caused by erosion, accompanied by thermal relaxation. © 2012 Elsevier Ltd.